2003
DOI: 10.1046/j.1365-2567.2003.01681.x
|View full text |Cite
|
Sign up to set email alerts
|

Rat C‐reactive protein activates the autologous complement system

Abstract: Activation of complement is a biological function of human C-reactive protein (hCRP), whereas rat CRP (rCRP) has been claimed to be unable to activate complement. As important biological functions of proteins are probably conserved among species, we re-evaluated, using various ligands, the capability of rCRP to activate complement. The activation of complement by hCRP and rCRP was investigated in solid- and fluid-phase systems. In the solid-phase system, purified CRP was fixed to enzyme-linked immunosorbent as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…A recent paper showed that neither human CRP nor rabbit CRP activated complement in serum from apolipoprotein E knockout mice, although in this case enzymatically modified low-density lipoprotein was used as the CRP ligand, not the PnC (30). Rat CRP does activate rat complement, but only if it is precipitated with PnC (28,31). Activation of complement by rat CRP occurs through the classical pathway because it binds to both rat and human C1q (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper showed that neither human CRP nor rabbit CRP activated complement in serum from apolipoprotein E knockout mice, although in this case enzymatically modified low-density lipoprotein was used as the CRP ligand, not the PnC (30). Rat CRP does activate rat complement, but only if it is precipitated with PnC (28,31). Activation of complement by rat CRP occurs through the classical pathway because it binds to both rat and human C1q (31).…”
Section: Discussionmentioning
confidence: 99%
“…Rat CRP does activate rat complement, but only if it is precipitated with PnC (28,31). Activation of complement by rat CRP occurs through the classical pathway because it binds to both rat and human C1q (31). Both plaice and lumpsucker CRP activate human complement (24), and trout CRP has been shown to activate trout complement (32).…”
Section: Discussionmentioning
confidence: 99%
“…The plasma concentration of CRP is increased in the presence of chronic inflammation, and there is a relationship between the circulating plasma concentration and subsequent cardiovascular events (de Beer et al, 1982;Yeh et al, 2001;Ridker et al, 2005). CRP is known to be involved in the local activation of the complement system (Volanakis, 1982;Diaz Padilla et al, 2003;Nijmeijer et al, 2003). Our previous studies showed that the crystalloid perfused isolated heart itself is capable of expressing mRNA and the rapid expression of complement proteins, as well as the membrane attack complex in response to ischemia/reperfusion injury (Yasojima et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…mice, rats, and humans) (9). CRP binds to pneumococcal C-polysaccharide (CPS) in humans; whereas in nonhumans, CRP binds to the surface of dead or dying cells (10). CRP which was first detected in 1930 by Tillet and Frances belongs to the pentraxin family of calcium-dependent ligand-binding plasma proteins, found in most vertebrates (e.g.…”
Section: Introductionmentioning
confidence: 99%